Circular RNAs: Novel potential regulators in embryogenesis, female infertility, and pregnancy‐related diseases. Issue 10 (20th April 2021) - Gao, Qinyu; Wang, Tianjuan; Pan, Linxin; Qian, Cheng; Wang, Juan; Xin, Qiong; Liu, Yajing; Zhang, Zhiguo; Xu, Yuping; He, Xiaojin; Cao, Yunxia
Abstract: Circular RNAs (circRNAs) are endogenous noncoding RNAs with unique cyclic structures. Although they were previously considered as nonfunctional transcription byproducts, numerous studies have demonstrated that circRNAs regulate gene transcription and expression via different mechanisms. Reproductive health influences the quality of life and affects offspring propagation in women. CircRNAs have been found to modify pregnancy‐related diseases, gynecologic cancers, polycystic ovary syndrome, aging, gamete, and embryo development. It's promising for circRNAs to be the novel diagnostic and therapeutic targets for multiple reproductive diseases. With the widespread application of assisted reproduction technology (ART), it has been revealed that circRNA identification contributes to estimating the quality of gametes and embryos, reflecting the success rate of ART. CRISPR‐Cas9 gene editing technology has enabled the discovery of new roles of circRNAs. So far, the roles of circRNAs in the reproductive system remain poorly defined. In this review, we describe the classification and functions of circRNAs in embryogenesis and the female reproductive system diseases, revealing potential roles of circRNAs physiologically and pathologically. In so‐doing, we provide ideas for developing circRNA‐based therapeutic treatment and clinical application of various female reproductive system diseases. Abstract : Circular RNAs (circRNAs) are endogenous noncoding RNAs with unique cyclic structures. CircRNAs have been found to modify pregnancy‐related diseases, gynecologic cancers, polycystic ovary syndrome, aging, gamete, and embryo development. It's promising for circRNAs to be the novel diagnostic and therapeutic targets for multiple reproductive diseases.